Variação dos compostos fenólicos e de cor dos vinhos de uvas (vitis vinifera) tintas em diferentes ambientes - Freitas, Dirce Maciel de (2006)
The quality of red wine was evaluated relating the variation of meteorological conditions such as color quantification and phenolic compound. Red wines of the cultivars Vitis vinifera, Cabernet Sauvignon, Merlot and Tannat, of the crops of 2003 and 2004 from the low-land (Santana do Livramento) or high-land (Bento Gonçalves) regions of the state of Rio Grande do Sul were analyzed. The phenolic compounds quantified were total flavonoids, anthocyanic flavonoids, non-anthocyanic flavonoids, total polyphenols, polymerized polyphenols, total anthocyanins and free anthocyanins. For the color were analyzed the color intensity and tonality and the chromatic parameters relative to the color spaces that were calculated from the tristimuli values, X, Y, and Z, based on the visible absorption spectra (400-700 nm) with 10nm of pause, on the illuminant D65 reading. The meteorological data related to the crop seasons of 2003 and 2004 were provided by 'Embrapa Uva e Vinho' (Agro meteorological station) in Bento Gonçalves and by 'Pernod Ricard' Brazil (meteorological station in Santana do Livramento). The wines of the cultivar Tannat of the crops of 2003 and 2004 has a high level of phenolic compounds, color intensity and chromatic parameters, due to the cultivar characteristics of having in its composition high level of anthocyanins, showing the red tint, while the wines of the cultivar Cabernet Sauvignon of the 2003 crop, from both regions has low level of phenolic compounds and low color intensity, showing a ruby tint. The 2004 crop in the low-land and high-land regions shows high level of phenolic compounds and color intensity, due to the climatic conditions favorable, dry, high insulation and with media temperature higher on the grapes maturation period, what provided a more complete maturation, mainly phenolic, while the 2003 crop presented a lot of precipitation and low insulation during the grapes maturation period.